Wireless network security a beginner's guide - Wrightson, Tyler (McGraw-Hill, 2012)
Protect wireless networks against all real-world hacks by learning how hackers operate. Wireless Network Security: A Beginner's Guide discusses the many attack vectors that target wireless networks and clients--and explains how to identify and prevent them. Actual cases of attacks against WEP, WPA, and wireless clients and their defenses are included. This practical resource reveals how intruders exploit vulnerabilities and gain access to wireless networks. You'll learn how to securely deploy WPA2 wireless networks, including WPA2-Enterprise using digital certificates for authentication. The book provides techniques for dealing with wireless guest access and rogue access points. Next-generation wireless networking technologies, such as lightweight access points and cloud-based wireless solutions, are also discussed. Templates, checklists, and examples give you the hands-on help you need to get started right away.